The enhancing performance of (Ba0.85Ca0.15Ti0.90Zr0.10)O3 ceramics by tuning anatase–rutile phase structure. (April 2016) - Chao, Xiaolian; Wang, Juanjuan; Wang, Zhongming; Zhang, Ting; Yang, Zupei; Li, Guangzhao
Graphical abstract: Titanium dioxide (TiO2 ) with different phase structure had interesting influence on the crystal structure, microstructure, the sintering temperature and electrical properties. Highlights: BCZT ceramics were prepared using either anatase or rutile structures as Ti source. Orthorhombic and tetragonal mixture structure was exhibited by adjusting Ti source. The optimal properties were observed in BCZT ceramics with rutile titanium dioxide. Abstract: To research effect of raw materials TiO2 with the phase structures on the crystal structure, microstructure and electrical properties of lead-free (Ba0.85 Ca0.15 )(Ti0.90 Zr0.10 )O3 (BCZT) ceramics, BCZT ceramics using either anatase or rutile as Ti source were synthesized by solid-state reaction. Titanium dioxide (TiO2 ) with anatase/rutile phase structures had interesting influence on the crystal structure, microstructure and the sintering temperature by the X-ray diffraction and SEM, which also played an important role in improved electrical properties. The BCZT ceramics with rutile titanium dioxide demonstrated optimal piezoelectric and dielectric properties: d 33 = 590 pC/N, k p = 0.46, ε r = 2810, tan δ = 0.014 and T c = 91 °C, which was obviously superior to BCZT ceramics with anatase titanium dioxide.